Heme oxygenase‐1 deficiency results in splenic T‐cell dysregulation in offspring of mothers exposed to late gestational inflammation. (27th February 2018) - Ozen, Maide; Zhao, Hui; Kalish, Flora; Yang, Yang; Folkins, Ann; Burd, Irina; Wong, Ronald J.; Stevenson, David K.
Abstract : Problem: Infection during pregnancy can disrupt regulatory/effector immune system balance, resulting in adverse pregnancy and fetal‐neonatal outcomes. Heme oxygenase‐1 (HO‐1) is a major regulatory enzyme in the immune system. We observed maternal immune response dysregulation during late gestational inflammation (LGI), which may be mediated by HO‐1. Here, we extend these studies to examine the immune response of offspring. Method of study: Pregnant wild‐type (Wt) and HO‐1 heterozygote (Het) dams were treated with lipopolysaccharide (LPS) or vehicle at E15.5. Pups' splenic immune cells were characterized using flow cytometry. Results: CD3 + CD4 + CD25 + (Tregs) and CD3 + CD8 + (Teffs) T cells in Wt and Het were similar in control neonates and increased with age. We showed not only age‐ but also genotype‐specific and long‐lasting T‐cell dysregulation in pups after maternal LGI. The persistent immune dysregulation, mediated by HO‐1 deficiency, was reflected as a decrease in Treg FoxP3 and CD3 + CD8 + T cells, and an increase in CD4 + /CD8 + T‐cell and Treg/Teff ratios in Hets compared with Wt juvenile mice after maternal exposure to LGI. Conclusion: Maternal exposure to LGI can result in dysregulation of splenic T cells in offspring, especially in those with HO‐1 deficiency. We speculate that these immune alterations are the basis of adverse outcomes in neonates from mothers exposed to low‐grade (subclinical) infections.